Experimental Investigation of Injection Strategies on Low Temperature Combustion Fuelled with Gasoline in a Compression Ignition Engine - Binbin Yang; Mingfa Yao; Zunqing Zheng; Lang Yue (Journal of Chemistry)
The present study focuses on the experimental investigation on the effect of fuel injection strategies on LTC with gasoline on a single-cylinder CI engine. Firstly, the engine performance and emissions have been explored by sweeping SOI1 and split percentage for the load of 0.9 MPa IMEP at an engine speed of 1500 rpm. Then, the double-injection strategy has been tested for load expansion compared with single-injection. The results indicate that, with the fixed CA50, the peak HRR is reduced by advancing SOI1 and increasing split percentage gradually. Higher indicated thermal efficiency, as well as lower MPRR and COV, can be achieved simultaneously with later SOI1 and higher split percentage. As split percentage increases, NOX emission decreases but soot emission increases. CO and THC emissions are increased by earlier SOI1, resulting in a slight decrease in combustion efficiency. Compared with single-injection, the double-injection strategy enables successful expansion of high-efficiency and clean combustion region, with increasing soot, CO, and THC emissions at high loads and slightly declining combustion efficiency and indicated thermal efficiency, however. MPRR and soot emission are considered to be the predominant constraints to the load expansion of gasoline LTC, and they are related to their trade-off relationship.